THE MEDIATING ROLE OF MSME CHARACTER IN THE INFLUENCE OF MSME LITERACY ON BUSINESS PERFORMANCE IN KARAWANG - Maula, Kholida Atiyatul; Suyaman, Dede Jajang; Piantara, Seia; Puspitaloka, Nina; Agustin, Ricky; Zahra, Syifa ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
This study aims to analyze the effect of MSME literacy on the Character and performance of MSMEs in Karawang Regency. MSME literacy encompasses knowledge of finance, business, law, and technology, which is believed to shape entrepreneurial Character and enhance business performance. The study employed a quantitative approach, utilizing a survey method with 100 MSME players. Data were analyzed using multiple regression and mediation tests. The results showed that MSME literacy has a positive and significant effect on the Character and performance of MSMEs. In addition, the Character of MSMEs is proven to partially mediate the relationship between Literacy and performance. The implications of this study encourage the need for an MSME literacy improvement program that is integrated with entrepreneurial character development.